EMPLOYEE GET MEMBER DI BADAN USAHA MILIK NEGARA (STUDI DI PT BANK RAKYAT INDONESIA (PERSERO) TBK KANTOR CABANG METRO (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2018)
This study was to describe (1) the component context: Destination Program Employee Get Member (2) input components: human resources, financial resources / budget and the means (3) components of the process: dissemination and implementation of the process of making a new account and (4) components product: the achievement of the number of products: fee-based income, funding structure and customer base. This study aims to identify and analyze the Evaluation of Program Implementation Employee Get Member in State Owned Enterprises studies PT Bank Rakyat Indonesia (Persero), Tbk Branch Metro 2014. The research method used is descriptive research type with qualitative approach. Data collection techniques in this study by observation, interview and documentation. The results of the evaluation study showed a context of close relevance between background issuance program with the objective to be achieved by stakeholder. However, in terms of quality or the readiness of the participants are still lacking, resources have not been adequate funding provided and the infrastructure provided is quite adequate.